Cell-free cyclization of delta-(L-alpha-aminoadipyl)-L-cysteinyl-D-valine to isopenicillin N. - Sawada, Y (1980)
Cell-free cyclization of delta-(L-alpha-aminoadipyl)-L-cysteinyl-D-valine to isopenicillin N by lytic enzyme extracts of Cephalosporium acremonium M-0198 was stimulated by ferrous ions. The optimum concentration of FeSO4 was 80 microM. No additional stimulation was observed with ascorbate, adenosine 5'-triphosphate, or alpha-ketoglutarate, but Triton X-100 and sonication of the extracts increased activity. ZnSO4 was very inhibitory to enzyme activity; CuSO4 was somewhat less inhibitory, and the least effective of the three was MnCl2. The dimer of the tripeptide was converted to a penicillin that has the biological spectrum of isopenicillin N, and this reaction was also stimulated by FeSO4. We found that sonication can be used directly to prepare extracts with cyclization activity from mycelia, without preparing protoplast lysates. The kinetics of cyclase appearance and disappearance during fermentation were similar to those of ring-expansion activity, i.e., enzyme appeared and peaked 13 h after growth ceased and then disappeared.